AFECTACIÓN DEL DERECHO A FRACCIONAR DEUDA TRIBUTARIA EN PROCEDIMIENTO DE COBRANZA COACTIVA ANTE EL SATT - Plasencia Namoc, Sofia Estefania (2018)
This research work is oriented to demonstrate, on the basis of doctrinal criteria, the affectation of the right to fractionation of tax debts in local governments in cases of coercive procedure with locked precautionary measure, Specifically, in the service of tax administration of Trujillo, and thus avoid undue restrictions to this right recognized in the section n) of article 92 of the tax code. It is also intended to demonstrate that there are no objective criteria to restrict the right to fractionation in cases of tax debt in coercive collection procedure with a precautionary measure, for this has been carried out a theoretical development of the right to Fractionation. We must bear in mind that the rules in force must be consistent with the constitutional principles of law, so that the interpretation and application of the rules cannot be contravened or violated. With this work, it is sought that the right to fraction of the tax debt in the coercive collection procedure be exercised by the taxpayers of the local governments in full, even when it has relapsed effective precautionary measure, always And when the collection of the debt or the auction of the goods has not been carried out, as is the case with the procedure followed in the SUNAT and before other district municipalities; thus avoiding to affect taxpayers with a desire to pay their debt although they do not have total cash Finally, we have reached the conclusion that a legislative reform in tax matters is necessary, in order to guarantee the taxpayer's rights, so that the taxable persons are benefited: the state because they will be paid the Taxes with their respective interests and the taxpayer because they can divide their debt, and cancel it without affecting their economy.